THE IMPACT OF AUTHORITARIAN AND EMPATHETIC COMMUNICATION ON EMOTIONAL REGULATION IN EARLY CHILDHOOD - Aprilia Doni Setiani; Arfina Hikmawati; Arifah Nabila Nur Mutiah; Cici Maisyaroh; Hery Setiyatna (STAI Nusantara Kota Banda Aceh, 2026)
This study discusses the impact of authoritarian and empathetic communication on the social, emotional, and communication development of early childhood children. Communication is an important aspect of parenting and education because it influences character building, self-confidence, emotional regulation, and children’s social interaction skills. This study employed a literature review method by analyzing various studies and theories related to communication patterns in early childhood. The findings indicate that authoritarian communication tends to be one-way, emphasizing commands, pressure, and strict control, which may cause children to become fearful, less confident, passive, and experience obstacles in socio-emotional development. In contrast, empathetic communication emphasizes understanding children’s feelings, active listening, and warm responses, which can improve children’s sense of security, social skills, emotional regulation, and confidence in expressing opinions. Furthermore, empathetic communication helps create more harmonious relationships between children, parents, and teachers. Therefore, parents and teachers are encouraged to apply empathetic communication accompanied by consistent discipline to support optimal early childhood development.